Exotic diboson Z′ decays in the U μν SSM - Aguilar Saavedra, J. A. (2021)
Searches for new leptophobic resonances at high energy colliders usually target their decay modes into pairs of light quarks, top quarks, or standard model bosons. Additional decay modes may also be present, producing signatures to which current searches are not sensitive. We investigate the performance of generic searches that look for resonances decaying into two large-radius jets. As benchmark for our analysis we use a supersymmetric U (1) ′ extension of the Standard Model, the so-called UμνSSM, where all the SM decay modes of the Z′ boson take place, plus additional (cascade) decays into new scalars. The generic searches use a generic multi-pronged jet tagger and take advantage of the presence of b quarks in the large-radius jets, and are sensitive to all these Z′ decay modes (except into light quarks) at once. For couplings that are well below current experimental constraints, these generic searches are sensitive at the 3 σ- 4 σ level with Run 2 LHC data.